Species diversity of Entamoeba and gastrointestinal parasites as co-infection in pigs in Kupang, East Nusa Tenggara, Indonesia - ‪Dony Chrismanto‬; ‪Nunuk Dyah Retno Lastuti‬; ‪Lucia Tri Suwanti‬; Poedji Hastutiek; Endang Suprihati; Dyah Ayu Kurniawati; ‪Aji Winarso‬ (Society for Indonesian Biodiversity, 2023)
Abstract. Chrismanto D, Lastuti NDR, Suwanti LT, Hastutiek P, Suprihati E, Kurniawati DA, Winarso A. 2023. Species diversity of Entamoeba and gastrointestinal parasites as co infection in pigs in Kupang, East Nusa Tenggara, Indonesia. Biodiversitas 24: 233-240. Protozoa Entamoeba spp. is the causative agent of amoebiasis that can infect humans and livestock. Several species that infect pigs are E. suis, E. polecki, E. histolytica, and E. coli. However, microscopic examination through morphological identification of parasites couldn't determine the genus and species level identity, leading to misdiagnosis. Therefore, molecular techniques are needed for accurate diagnosis with species-specific primers. In this study, 100 fecal samples were collected from pig farms in Kupang, East Nusa Tenggara Province, Indonesia. This study aims to identify, using molecular techniques, the presence of Entamoeba spp. with the SSUrRNA gene as a marker to determine the diversity of Entamoeba species in pigs and to detect co-infection with other gastrointestinal parasites in Kupang. The result was found: E. suis 98% (98/100), E. polecki 44% (44/100), E. polecki ST3 10% (10/100), and E. coli 20% (30/100) spread on pig farms in 8 villages in Kupang. Furthermore, E. polecki ST3 and E. coli finding show that pigs in several areas in Kupang are infected with potentially zoonotic species. In addition to finding various species of Entamoeba by Polymerase Chain Reaction (PCR) amplification, based on microscopic examination, other gastrointestinal parasites were also found as co-infections, namely: Eimeria sp. (34%), Cystoisospora suis (30%), Strongyloides sp. (34%), Oesophagostomum sp. (51%), Metastrongylus sp. (18%), and Trichuris suis (8%). That is the first report concerning mixed infections with E. suis, E. polecki ST3, E. coli, and other gastrointestinal parasites in pigs in Kupang, Indonesia.